Annulment of Arbitral Awards: A New Adoption of the UNCITRAL Model Law’s Legal Framework - Hisham Al Hyari, Omar (2020)
For several years, the United Arab Emirates (UAE), specifically Dubai, has been the heart of arbitration in the Middle East. This position was enhanced by the UAE legislature in May 2018 through the enactment of Federal Law No. 6, which made the UAE the 81st country to adopt the United Nations Commission on International Trade Law (UNCITRAL) Model Law on International Commercial Arbitration. The aforementioned federal law provides a new legal framework for the annulment of arbitral awards in the country. Mean while, it is a fact that most arbitral awards in the UAE face nullification challenges. It is also a fact that the nullification of arbitral awards causes considerable waste in terms of time and expenses. Therefore, this paper aims to identify and analyze the grounds for nullifying arbitral awards under the aforementioned federal law.